Biomarkers of Brain Damage: S100B and NSE Concentrations in Cerebrospinal Fluid--A Normative Study - Hajduková, Lenka; Sobek, Ondřej; Prchalová, Darina; Bílková, Zuzana; Koudelková, Martina; Lukášková, Jiřina; Matuchová, Inka (BioMed research international, 2015)
NSE and S100B belong among the so-called structural proteins of the central nervous system (CNS). Lately, this group of structural proteins has been profusely used as specific biomarkers of CNS tissue damage. So far, the majority of the research papers have focused predominantly on the concentrations of these proteins in blood in relation to CNS damage of various origins. Considering the close anatomic and functional relationship between the brain or spinal cord and cerebrospinal fluid (CSF), in case of a CNS injury, a rapid and pronounced increase of the concentrations of structural proteins specifically in CSF takes place. This study inquires into the physiological concentrations of NSE and S100B proteins in CSF, carried out on a sufficiently large group of 601 patients. The detected values can be used for determination of a normal reference range in CSF in a clinical laboratory diagnostics.
Keywords: Young Adult; Male; biologické markery; Sex Characteristics; Biomarkers; mladý dospělý; Brain; Adult; dospělí; mužské pohlaví; S-100 kalcium vázající protein G, podjednotka beta; pohlavní dimorfismus; S100 Calcium Binding Protein beta Subunit; lidé; ženské pohlaví; fosfopyruváthydratasa; Humans; Phosphopyruvate Hydratase; mozek; Age Distribution; věkové rozložení; Female; lidé středního věku; Middle Aged